The Relationship Between Attitudes, Vulva Hygiene And Diet With The Incidence Of Vaginal Discharge In Students Of The Midwifery Study Program At Universitas Kader Bangsa Palembang In 2022 - Titin Satriani; Fika Minata Wathan; Titin Dewi Sartika Silaban; Merisa Riski; Syarifah Ismed (JURNAL KEBIDANAN KESTRA (JKK), 2022)
One of the reproductive health problems in adolescent girls is vaginal discharge. This research is correlational analytic research with cross sectional approach. The sample was selected using purposive sampling with a sample of 40 respondents. Collecting research data using a questionnaire. Data analysis.was carried out in several stages, namely univariate analysis and also bivariate analysis using the Chi-Square test. Based on the results of the analysis showed that there was a significant relationship between attitudes (P-value 0.027), vulvar hygiene (P-value 0.001) and eating patterns (P-value 0.005) on the incidence of vaginal discharge. There is a relationship between attitudes, vulvar hygiene and eating patterns with the incidence of vaginal discharge in the midwifery study program students of UKB Palembang in 2022.